2020
DOI: 10.1503/cjs.005619
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon clinical practice variation and patient preferences during the informed consent discussion: a mixed-methods analysis in lumbar spine surgery

Abstract: Background: Patients with lumbar disc herniation may greatly benefit from microdiscectomy. Although spine surgeons performing microdiscectomy routinely obtain informed consent, the potential adverse events they disclose often vary. Moreover, little is known about what disclosures are deemed most valuable by patients. The aim of this mixed-methods study was to determine practice variations among spine surgeons in regard to the disclosure of potential adverse events during informed consent discussions for lumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…One study explored the sources of expectations in patients undergoing lumbar sur-gery 9 Another study used both surgeon and patient interviews to determine variations in disclosure of adverse events during informed consent for lumbar microdiscectomy pro-cedures. 10 While both offer insight into improved processes for SDM, the current literature does not address how SDM may influence patient satisfaction and decisional regret. A previous study by our group showed that one in five patients expressed decisional regret following deformity correction surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study explored the sources of expectations in patients undergoing lumbar sur-gery 9 Another study used both surgeon and patient interviews to determine variations in disclosure of adverse events during informed consent for lumbar microdiscectomy pro-cedures. 10 While both offer insight into improved processes for SDM, the current literature does not address how SDM may influence patient satisfaction and decisional regret. A previous study by our group showed that one in five patients expressed decisional regret following deformity correction surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the spine literature are limited to specific elements of decision-making or patient education. One study explored the sources of expectations in patients undergoing lumbar sur-gery 9 Another study used both surgeon and patient interviews to determine variations in disclosure of adverse events during informed consent for lumbar microdiscectomy pro-cedures 10 . While both offer insight into improved processes for SDM, the current literature does not address how SDM may influence patient satisfaction and decisional regret.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these legal and ethical obligations, executing the informed consent process remains a challenge, especially in orthopedic surgery [8]. Malpractice claims often highlight inadequate disclosure of procedure risks [9], a deficiency attributed to various factors such as physicians' aversion to delivering negative news, emotional discomfort, uncertainty regarding outcomes, and time constraints, particularly in urgent cases such as hip fractures [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, failure to disclose the risks of a procedure in the informed consent process is associated with increased indemnity risk [5]. In contrast, there is evidence that well-informed patients are more satis ed, have a more effective recovery, and le fewer legal claims [9].…”
Section: Introductionmentioning
confidence: 99%